Pengaruh Model Pembelajaran Think Pair Share Terhadap Keaktifan Belajar PAK Siswa Kelas IX di SMP Negeri 4 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Melli Agustina simanjutak; Malani Simanungkalit; Dame Taruli Simamora; Damayanti Nababan; Raikhapoor Raikhapoor (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The study aims to determine the positive and significant influence of the Think Pair Share learning model on the learning activity of grade IX students of SMP Negeri 4 Tarutung for the 2023/2024 Learning Year. The research hypothesis is that there is a positive and significant influence between the Think Pair Share learning model on the learning activity of grade IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 Learning Year. Descriptive and inferential quantitative research methods. The population of all grade IX students of SMP Negeri 4 Tarutung for the 2023/2024 Learning Year who are Protestant Christians is 101 people. Random sampling is 40% of the total population, which is 40 people. The research instrument is in the form of a closed questionnaire. The results of data analysis were obtained: a) Value rhitung=0.643>rtabel=0.312 and thitung=5.175>ttabel=2.021 shows a positive and significant relationship between the Think Pair Share learning model and the PAK learning activity of grade IX students of SMP Negeri 4 Tarutung Learning Year 2023/2024. b) Regression equation . c) The determination test is known to have an effect of 41.34%. d) Test the hypothesis obtained Fcalculate = 26.857 > Ftable = 3.23 then H0 is rejected and Ha is accepted. The study concluded that there is a positive and significant influence between the Think Pair Share learning model on the learning activity of grade IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 Learning Year